Rejser og forandring: Intersektioner af klasse, køn og etnicitet - Yvonne Mørck; Bente Rosenbeck (Kvinder, Køn & Forskning, 2010)
Travels and change: Intersections of class, gender and ethnicity. The article presents and discusses various aspects of the ‘class travel’ concept. It begins with a description of the class journey into Academia undertaken by two contemporary women. A female ‘gender travel’ is exemplified by the first female academics to study at Copenhagen University in 1875. A group of girls from the 1950s East End of London, who received a longer schooling, represents both a class and gender journey. In the ‘New East End’ in the 1990s, however, ethnicity is in focus – in intersection with class and gender. The aim of this contribution is to illuminate the interweaving of gender, class and ethnicity in both a historical and contemporary perspective in relation to education on all levels.